PcrA Dissociates RecA Filaments and the SsbA and RecO Mediators Counterbalance Such Activity - Carrasco, Begoña; Moreno-del Álamo, María; Torres, Rubén; Alonso, Juan Carlos (Frontiers in Molecular Biosciences, 2022)
PcrA depletion is lethal in wild type Bacillus subtilis cells. The PcrA DNA helicase contributes to unwind RNA from the template strand, to backtrack the RNA polymerase, to rescue replication-transcription conflicts and to disassemble RecA from single-stranded DNA (ssDNA) by poorly understood mechanisms. We show that in the presence of RecA, circa one PcrA/plasmid-size circular ssDNA (cssDNA) molecule hydrolyzes ATP at a rate similar to that on isolated cssDNA. PcrA K37A, which poorly hydrolyses ATP, fails to displace RecA from cssDNA. SsbA inhibits and blocks the ATPase activities of PcrA and RecA, respectively. RecO partially antagonizes and counteracts the negative effect of SsbA on PcrA- and RecA-mediated ATP hydrolysis, respectively. Conversely, multiple PcrA molecules are required to inhibit RecA·ATP-mediated DNA strand exchange (DSE). RecO and SsbA poorly antagonize the PcrA inhibitory effect on RecA·ATP-mediated DSE. We propose that two separable PcrA functions exist, an iterative translocating PcrA monomer strips RecA from cssDNA to prevent unnecessary recombination with the mediators SsbA and RecO balancing such activity; and a PcrA cluster disrupts DNA transactions, as RecA-mediated DSE.